Effect of Vestibular Stimulation on Postural Stability and Mobility in Elderly - Jain Ankit1 , Sarkar Aparna2 , Gupta Meena3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Galvanic vestibular stimulation (GVS)is proven to be a promising tool to improve vestibular functioning.Decline in vestibular functioning in the elderly results in decreased capacity to identify weak signal whichmay lead to postural instability. Postural sway is produced when GVS is given over mastoid process. Inthis study our aim is to determine whether GVS can be utilized to maximize the effect of balance trainingprogramme among elderly individuals. Ambulatory community dwelling elderly (N=150, age 65.67±3.4yrs) were randomly assigned to a control group (Group A, n=50, age 65.54±3.4 yrs), Placebo group (GroupB, n=50, age 65.5±3.3 yrs) and an experimental group (Group C, n=50, age 65.98±3.5 yrs). Group A wasnot given any intervention while group B was given placebo stimulation along with balance training andgroup C was given noisy galvanic vestibular stimulation along with balance training program. Pre, mid andpost data were recorded for overall stability index (OSI) (Biodex Balance Master) and Timed up and gotest(TUG) and analyzed. Compared to control group there was a significant improvement in overall stabilityand mobility in placebo and experimental groups. Significant difference was observed in improvement inexperimental group compared with placebo group for both,OSI and TUG. Early improvement in stabilityand mobility was also observed in experimental group but similar results were not obtained in control andplacebo groups. The outcome of this study suggests that GVS can be utilized therapeutically to optimize theefficacy of balance training clinically.